Tanggung Jawab Gembala Jemaat terhadap Perkawinan Adat Belangin Mapak Pue Tetek Mando di GKSI Jemaat Getsemani Sebangar Kecamatan Kuala Behe - Eliantri Putralin; Marlina; Esau Yesyurun Tang (Pusat Riset dan Inovasi Nasional, 2024)
Congregation members are God's people who should be cared for and shepherded by the pastor of the congregation. Because without being shepherded well and responsibly, God's people are easily influenced to carry out and maintain a culture of belief that is contrary to the truth of God's Word. Indeed, the truth of God's Word is the main source for organizing human life in the world, including the people of God in the Indonesian Faithful Christian Church (GKSI) Sebangar Congregation, Kuala Behe ​​District. In order for God's people in the GKSI Sebangar Congregation, especially the young men and women who are old to marry well without violating customary laws relevant to God's Word, the pastor's responsibility in shepherding is needed to be maximal and optimal. The pastor's responsibility as a Christian educator of the GKSI Sebangar Congregation regarding the mapak pue tetek mando traditional marriage is considered important because some young men and women after the mapak pue tetek mando event immediately marry like husband and wife without paying attention to Christian marriage. This study aims to describe the Belangin mapak pue tetek mando traditional marriage in the Sebangar area. The researcher used qualitative methods through observation, interviews, and literature review. The results indicate that pastors, as Christian educators, are increasingly loyal in their responsibility to shepherd all members of the GKSI Gethsemane Sebangar congregation, enabling young men and women of marriageable age to maintain a pure life.